Morphological Signs of Acute Lung Injury of Varying Etiology (Experimental Study) - V. V. Moroz; A. M. Golubev; Yu. V. Marchenkov; Yu. A., Gorodovikova; Yu. G. Zorina; D. V. Lysenko; D. V Sundukov; P. Shaman (Общая реаниматология)
Objective: to reveal pulmonary morphological changes in acute lung injury (ALI) of varying etiology. Material and methods. An experiment was carried out on 4 groups of albino non-inbred male rats weighing 300—400 g. The following ALI models were 1) acidin-pepsin solution (PH-1.2) aspiration; 2) blood aspiration; 3) blood loss (50% circulating blood volume) concurrent with vascular thrombosis in the microcirculatory bed; 4) artificial ventilation-induced ALI. The duration of the study was 1 hour to 3 days. Histological lung slices were stained with hematoxylin and eosin; a Schiff reaction was conducted. Results. All the animals developed interstitial edema, exhibited desquamation of the bronchial epithelium; damage to the capillary endothelium and basement membranes; segmental leukocyte, macrophage, and lymphocyte infiltration of intraalveolar septa, atelectases, hemorrhages, and sludges. Conclusion. Morphological signs in ALI are nonspecific and they do not depend on an etiological factor. Morphological changes in ALI result in damage to the endothelium of lung capillaries and their basement membranes, higher capillary permeability, extravascular fluid accumulation, and protein exudation with the development of noncardiogenic pulmonary edema. Key words: acute lung injury, blood loss, artificial ventilation, aspiration.